Konstruksi Genosida Palestina Melalui Fotografi Motaz Azaiza di Media Sosial Instagram - Wisnu Batara Nursulistyo Adhy; Farikha Rachmawati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to analyze the representation of the Palestinian genocide through photographic works uploaded by @Motaz_Azaiza on Instagram. Using a qualitative method with Charles Sanders Peirce's semiotics approach, this research focuses on analyzing visual elements such as gestures, scenes, colors, and social contexts in eight selected photos. The findings reveal that Motaz Azaiza's photographs effectively represent the impacts of the Palestinian genocide, both physically and emotionally, through visual symbolism such as ruined buildings, victims' expressions, and social narratives. As a medium of visual communication, these works not only document events but also serve as advocacy tools to raise global awareness, foster empathy, and encourage tangible actions toward humanitarian issues. By utilizing Instagram, these photos reach a broader audience, demonstrating how photojournalism can act as an effective medium in strengthening global solidarity for humanitarian tragedies. This study provides insight into the crucial role of conflict visualization in creating narratives relevant to the social media era.